4D Printing: A Material Combination Concept to Realize 4D Printed Products with Newly Emerging Property/Functionality (Adv. Sci. 9/2020). Issue 9 (6th May 2020) - Wu, Hongzhi; Zhang, Xuan; Ma, Zheng; Zhang, Ce; Ai, Jingwei; Chen, Peng; Yan, Chunze; Su, Bin; Shi, Yusheng
Abstract : In article number 1903208, Chunze Yan and co‐workers propose a material combination concept, by combining additively manufactured magnetic and electrical building blocks, to construct new 4D printed products. The integrated 4D printed devices show a controllably changed piezoelectric property under the exerted external pressure, as well as new functionality of working as self‐powered pressure‐sensitive monitors.